Les riches heures et l’avenir incertain de la culture cotonnière en Afrique de l’Ouest et du Centre - Camille Renaudin (EchoGéo)
Cotton farming has been one of the rare achievements in the agricultural development of Western and Central African CFA franc countries in the second half of the twentieth century. However, the economical crisis is now facing threats that jeopardize its future and shows the difficulty for African cotton industries to integrate the global market. It also reveals the inherent constrains to African countries environments. As much factors - exogenous and endogenous – that the actors involved in these industries have to consider in order to promoting a long term improvement of their production. The stake is to maintain an income for millions of families in these African rural regions.